Effect of feeds and feeding levels over different time periods on the rate of ammonia excretion in Macrobrachium rosenbergii (de Man) - Panikkar, Preetha; Ayyar, S P; Khatre, Shakuntala (Indian Journal of Fisheries, 2016)
The rate of ammonia excretion in Macrobrachium rosenbergii at 2, 4 and 6 h, when fed three commercial feeds and two control feeds at 1%, 5% and 10% of body weight, were investigated. The rate of ammonia excretion was significantly influenced by the quality of feed offered. A higher rate of ammonia excretion by the prawns fed on control feeds as compared to the commercial feeds appears to be correlated with the protein content in the feeds offered. The quantity of food consumed had significant influence on the ammonia excretion and it was found to increase with feed levels.